2015
DOI: 10.1080/09205063.2015.1007413
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically cross-linked hyaluronic acid/graphene oxide nanocomposite hydrogel with pH-responsive release

Abstract: Hyaluronic acid (HA) is made up of repeating disaccharide units (β-1,4-d-glucuronic acid and β-1,3-N-acetyl-d-glucosamine) and is a major constituent of the extracellular matrix. HA and its derivatives which possess excellent biocompatibility and physiochemical properties have been studied in drug delivery and tissue engineering applications. Tyramine-based HA hydrogel with good compatibility to cell and tissue has been reported recently. However, inferior mechanical property may limit the biomedical applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The combination of GO with hydrogels was described previously in another drug delivery context. GO-based hydrogels present functional properties, for instance, pH-responsiveness, good mechanical properties, and thermal stabilities [60]. Thus this combination was tested, i.e., in curing bacterial infections in the gastrointestinal tract [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of GO with hydrogels was described previously in another drug delivery context. GO-based hydrogels present functional properties, for instance, pH-responsiveness, good mechanical properties, and thermal stabilities [60]. Thus this combination was tested, i.e., in curing bacterial infections in the gastrointestinal tract [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Graphene and its derivatives have attracted considerable interest due to their unique 2-D structure that provides a large surface area for π–π stacking [ 83 , 84 , 85 , 86 ]. The functional groups attached to GO sheets such as epoxy, hydroxyl, and carboxylic acid facilitate easy modification [ 87 ] and facilitate the dispersion of GO in specific polymer matrices or polar monomers during in situ polymerization [ 88 ].…”
Section: Carbon Nanomaterials Conjugated With Hyaluronic Acid For Drug Deliverymentioning
confidence: 99%
“…Song et al employed another biomolecule hyaluronic acid to prepare nanocomposite hydrogel with GO through horseradish peroxidase catalyzed in situ cross-linking process. 399 Compared to pure hyaluronic acid hydrogel, mechanical stability of the composite gel was Several other groups have also reported potential dye removal application of GO-based gel-nanocomposites. Li et al reported functionalization of poly(vinyl alcohol) (PVA) hydrogels with GO for dye removal applications.…”
mentioning
confidence: 99%